AN ANALYSIS OF BORROWING WORD IN DESTINASIAN INDONESIA MAGAZINE - Muziatun Muziatun; Jefriyanto Saud; Nurul Ain Halada (University of Kuningan, 2021)
Borrowing word is a word from another language which is adopted by another language as stated by Nelson Francis (1965). In instances, people in Indonesia tends to borrow other language in order to describe a thing or situation. Nowadays, the borrowing language can be famous and familiar to others through the use media mass. This fact can influence other in order to use the foreign language than the native language. Due to the fact, this research aims to analyze the borrowing language on media mass especially in Tourism Magazine. The DestinAsian Magazine become the appropriate source of data in order to identified what types of borrowing word that usually occurred in media mass. Moreover, the Bloomfield theory (1935) become the main theory which to identified the types of borrowing through the sociolinguistics and phonetic perspective. This research uses qualitative method to analyze the data. As the result, there are 425 words which identified as borrowing word from English language in DestinAsian Indonesian Magazine. However, after checked the identified loan word in Kamus Istilah Pariwisata there are only 25 words that can be analyze as the data which is 6 words categorized as cultural borrowing, 13 words categorized as intimate borrowing, and 6 words categorized as dialect borrowing. Toward the result it can be conclude that the high tendency of using borrowing word from foreign language than the use Indonesian Language.Keywords: Borrowing words; types of borrowing word